A cyanogenic glucoside of Trifolium repens deters oviposition by the common grass yellow Eurema mandarina. (4th July 2019) - Ohashi, Toshiki; Ohta, Shinji; Ômura, Hisashi
Abstract: The common grass yellow Eurema mandarina (Pieridae, Coliadinae) widely inhabits Japan, feeds on various fabaceous plants such as silktree ( Albizia julibrissin ) and uses d ‐pinitol, a cyclitol omnipresent in Fabaceae, as a primary oviposition stimulant. However, E. mandarina has a clear host preference within the Fabaceae; for example, white clover ( Trifolium repens ) is a nonhost despite containing d ‐pinitol. The present study aims to identify plant chemicals in white clover that inhibit oviposition of E. mandarina . Females lay very few eggs on T. repens foliage and plastic plant models treated with a methanolic extract of the foliage. The foliage extract is fractionated by successive extraction with chloroform, isobutanol and water. None of these fractions induce egg‐laying responses. The aqueous fraction is further separated into four subfractions (Tr‐3‐1 to Tr‐3‐4) by column chromatography. Among these subfractions, females show high egg‐laying responses to Tr‐3‐1, which is known to contain d ‐pinitol. Interestingly, Tr‐3‐2, when mixed with Tr‐3‐1, significantly decreases egg‐laying responses, indicating that it contains oviposition deterrents. Chemical analyses reveal that two cyanogenic glucosides, linamarin and lotaustralin, are the major constituents of Tr‐3‐2. Authentic linamarin does not elicit egg‐laying responses and significantly inhibits female oviposition when mixed with Tr‐3‐1 at the natural concentration. Although these cyanogenic glucosides are reported to synergistically induce oviposition of a coliadine species Colias erate on white clover, we conclude that linamarin acts as an oviposition deterrent for E. mandarina, restricts its host range and regulates their differential host acceptance. Abstract : The common grass yellow Eurema mandarina lays few eggs on fresh leaves of Trifolium repens and an artificial model treated with its methanolic extract. Among the four chromatographic aqueous subfractions of the leaf extract, the most polar subfraction, Tr‐3‐1, strongly induces female oviposition, whereas the second most polar subfraction, Tr‐3‐2, significantly suppresses it. The subfraction Tr‐3‐2 contains linamarin as a major constituent and this cyanogenic glucoside serves as an oviposition deterrent for E. mandarina .